Duration of acetowhitening as a novel objective tool for diagnosing high risk neoplasia in Barrett’s esophagus: a prospective cohort trial - Longcroft-Wheaton, G.; Brown, J.; Basford, P.; Cowlishaw, D.; Higgins, B.; Bhandari, P. (Endoscopy, 2013)
Background and study aims: Acetic acid reacts with Barrett’s mucosa to produce acetowhitening which disappears with time. The clinical significance of this is unknown. We aimed to quantify the acetowhitening time, developing an objective tool for diagnosis of neoplasia in Barrett’s esophagus. Patients and methods: Prospective cohort study in a tertiary referral center, enrolling patients undergoing surveillance of Barrett’s metaplasia or referred with suspected neoplasia. Acetic acid 2.5 % was applied to the mucosa via a spray catheter. Acetowhitening was observed and time to disappearance recorded. Targeted biopsies of any neoplasia and quadrantic 2-cm biopsies of residual Barrett’s area were then taken. Histological findings were investigated in relation to duration of acetowhitening.Results: 132 patients were examined. A receiver operating characteristic (ROC) curve was produced for identifying high risk neoplasia according to acetowhitening duration. The area under the curve (AUC) was 0.93 (0.89 – 0.97). Using a threshold of 142 seconds yielded a sensitivity for neoplasia of 98 % (95 % confidence interval [95 %CI] 89 % – 100 %) and specificity of 84 % (74 % – 91 %). The ROC curve for mucosal neoplasia (high grade dysplasia or intramucosal carcinoma) versus deep invasive cancer showed an AUC of 0.786 (0.61 – 0.96); a cutoff of 20 seconds yielded a sensitivity and specificity for invasive cancer of 67 % (35 % – 90 %) and 85 % (69 % – 95 %), respectively. Conclusion: The time to disappearance of acetowhitening can serve as a simple but very sensitive tool for the diagnosis of high risk neoplasia in Barrett’s esophagus. It can be used to distinguish mucosal neoplasia from deep invasive cancer.